2018
DOI: 10.1111/jog.13701
|View full text |Cite
|
Sign up to set email alerts
|

Case for a role of the microbiome in gynecologic cancers: Clinician's perspective

Abstract: In this review, we aimed to provide insight into the microbiome and its association with endometrial and ovarian cancer and their risk factors. We reviewed the literature focusing on the relationship between the microbiome and cancer, as well as the relationship between gynecologic diseases and cancers. The human body contains different kinds of microorganisms in various body parts, which is termed the microbiome. The number of microorganisms that live in and on the human body is greater than that of the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 117 publications
0
21
0
2
Order By: Relevance
“…First, an analysis24 of the microbiota of ovarian cancer tissue samples and matched non-cancerous tissue showed that two bacterial phyla, namely Proteobacteria and Firmicutes, were predominant in the cancer samples but not in the control samples. Second, inflammation caused by such agents as Proteobacteria and Firmicutes, and the subsequent release of bacterial toxins such as colibactin and cytolethal distending toxin, could directly damage the cellular DNA by causing doublestranded breaks and thereby activating the DNA damage checkpoint pathway 25. Third, the protective mechanism of interventions that reduce ovarian cancer risk could be mediated, at least partly, by modulation of the microbiota.…”
mentioning
confidence: 99%
“…First, an analysis24 of the microbiota of ovarian cancer tissue samples and matched non-cancerous tissue showed that two bacterial phyla, namely Proteobacteria and Firmicutes, were predominant in the cancer samples but not in the control samples. Second, inflammation caused by such agents as Proteobacteria and Firmicutes, and the subsequent release of bacterial toxins such as colibactin and cytolethal distending toxin, could directly damage the cellular DNA by causing doublestranded breaks and thereby activating the DNA damage checkpoint pathway 25. Third, the protective mechanism of interventions that reduce ovarian cancer risk could be mediated, at least partly, by modulation of the microbiota.…”
mentioning
confidence: 99%
“…c The relative abundance of Anoxynatronum sibiricum (Control group: n = 10, cancer group: n = 6, P = 0.034, Mann-Whitney U test). d The relative abundance of Methanosarcina vacuolata (Control group: n = 10, cancer group: n = 6, P = 0.001, Mann-Whitney U test) mechanisms that tubal ligation impairs circulation of bacteria that are associated with ovarian cancer risk between the lower and upper genital tract [26]. Second, the bacteria in the upper female reproductive tract, including the ovaries, may be endosymbiotic and separated from other bacteria and the outside environment [4].…”
Section: Discussionmentioning
confidence: 99%
“…Gynecological cancers have also been associated with microbiome constitution [41]. A study compared the microbiomes from different sites of the female reproductive tract (vaginal, uterine, Fallopian tubes, and ovarian samples) between women with endometrial cancer, endometrial hyperplasia, or benign uterine alterations.…”
Section: Microbiome and Cancermentioning
confidence: 99%